Characterizing Instructional Leader Interactions in a Social Learning Management System using Social Network Analysis - Llantos, Orven E (Archīum Ateneo, 2019)
Online learning environments are designed with specific users and respective roles in mind. However, for social systems that thrive on the interaction between and among users, important features are developed based on relationships that evolve over time. Typical learning management systems are designed with the teacher and the student as primary users of the system. my.eskwela is a social learning management system that has been designed for use in public schools in the Philippines with the inclusion of an additional user, the school administrator. Although administrators influence on student learning through mediated effects of instructional leadership, pieces of literature are few that provide evidence of their presence in the learning environment, specifically in the implementation of sLMS. By applying Social Network Analysis in the interaction logs from a sLMS that includes instructional leaders in its implementation, this paper aims to answer the question: Can instructional leadership be manifested in social system interactions? Using measures of centrality in social network analysis, results show that administrators play a key role in the network as main drivers of the network information flow. The results affirm the explicit presence of instructional leadership in the implementation of my.eskwela. In addition, sLMS should provide a means for administrator to monitor activities in enforcing mediated learning to students. Contribution of this study is on the the method to verify the instructional leadership of administrators in its inclusion in the implementation of sLMS.